Design and prototype of a micro hydrokinetic vertical turbine (2017)
In Latin America only few countries are 100% connected to national electric networks. In Colombia, 52% of the national territory is known as NonInterconnected Zones with a population of 2 million people. To cover these zones basic electricity needs, the use of natural, local and renewable resources such as the hydraulic is proposed, due to the high energetic potential. For this purpose, there are several types of hydraulic turbines, most of them used for large scale power generation (UPME, 2010). This paper aims to design of hydraulic turbomachines for micro-generation to satisfy the electricity demand on isolated villages is deeply research. To accomplish this, a three straight blades Vertical Axis Micro Turbine H-Darrieus type is designed and modelled using CAD computational tools. Hydraulic characterization is run on a CFD ANSYS module and fluid-structure interaction is analyzed. Prototyping is made using 3D-printing process in a digital fabrication lab